MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TRANSFORMATIF BERBASIS DIGITAL TERINTEGRASI UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Ummi Kulsum; Nur Cholid; Muhammad Ahsanul Husna (STKIP Subang, 2026)
The advancement of digital technology demands a methodological reconstruction in Islamic Religious Education (PAI) in elementary schools, which has long been criticized for being conventional, dogmatic, and lacking in stimulating students' critical reasoning. This study aims to formulate and analyze the effectiveness of the